The Role of Knowhow Acquisition in the Formation and Duration of Joint Ventures - Habib, Michel A.; Mella-Barral, Pierre (Review of Financial Studies, 2007)
We analyze the role of knowhow acquisition in the formation and duration of joint ventures. Two parties become partners in a joint venture to benefit from each other’s knowhow. Joint operations provide each party with the opportunity to acquire part of its partner’s knowhow. A party’s increased knowhow provides the impetus for the dissolution of the joint venture. We characterize the conditions under which dissolution takes place, identify the party that buys out its partner, determine the time to dissolution, establish its comparative statics, and examine the implications of knowledge acquisition for the desirability of joint venture formation. (JEL code: G34)